The use of didatic games to motivate students from eight to ten to participate into the efl classroom - Pauta, Cecilia; Cabrera, Sandra
This work is focused on didactic games to motivate children?s participation during their English learning process. Didactic games are strategies which allow students to develop their cognitive and creative abilities. Using games into the EFL classroom helps to improve learning in students. As Brumfit, Moon, and Tongue have stated, didactic activities enhance pupils to acquire the language in a natural way. Therefore, didactic games become effective tools in order to develop language skills. Based on Piaget´s theory, children acquire knowledge through physical, logical, mathematical, and social interaction, which help them to understand and assimilate how their world works. Didactic games thus provide children opportunities to acquire new experiences, which allow them to know their world. They also, as it is the purpose of this monograph, encourage pupils towards learning English as a foreign language, since they find games fun and interactive. These games are not only focused on the English language itself but on different topics which children enjoy.